The Degree of Computer Literacy Availability among Educational Qualification Diploma Students at the Faculty of Education, Tishreen University -A Field Study - طراف, حازم; خضر علي; نسرين خضار (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The current research aimed to identify the degree of availability of computer literacy among educational qualification diploma students at the Faculty of Education at Tishreen University, as well as to detect statistically significant differences in the level of computer literacy among educational qualification diploma students according to the following variables (sex, college, following training courses in the field of computer, owning a personal computer). The researcher used the descriptive approach, and the tool was a questionnaire (prepared by the researcher and judged by specialists and studied for its validity and reliability), as it was applied to a sample of (178) students from the educational qualification diploma students at the Faculty of Education at Tishreen University. The results of the research showed that the total degree of computer literacy among educational qualification diploma students at the Faculty of Education at Tishreen University was medium, and that there was no difference in the level of computer literacy among educational qualification diploma students according to the gender variable, while there was a difference in the level of computer literacy The educational qualification diploma students have according to the variable of the college (in favor of the scientific colleges), and according to the variable of computer training courses (in favor of the students who followed training courses in the computer), and according to the variable of owning a personal computer (in favor of the students who own a personal computer).